2020
DOI: 10.1111/jcpp.13206
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of healthcare utilization and costs of psychiatric and somatic multimorbidity in adults with childhood ADHD: a prospective register‐based study

Abstract: BackgroundA better understanding of the trajectories and economic burden of psychiatric and somatic disorders (multimorbidity) in ADHD from childhood to adulthood is important for guiding more targeted areas for treatment of ADHD and prevention of multimorbidity, and for forecasting demands on the medical infrastructure. This study aimed to investigate patterns of healthcare utilization and costs of multimorbidity across young adulthood in individuals with a childhood ADHD diagnosis, and additionally in indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 40 publications
2
17
0
1
Order By: Relevance
“… 6 Although there is a plethora of research that has shown the frequent co-occurrence of psychiatric disorders with ADHD, 7 associations with physical health conditions have been less studied, despite health-care costs in ADHD being substantially driven by both psychiatric and physical comorbid conditions. 8 , 9 Physical conditions that have shown robust and replicated association with ADHD, especially in childhood, include metabolic disorders, sleep disorders, and asthma. 10 A few studies have suggested tentative associations between ADHD and dementia, 11 diseases of the basal ganglia and cerebellum (eg, Parkinson's disease), 12 and cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“… 6 Although there is a plethora of research that has shown the frequent co-occurrence of psychiatric disorders with ADHD, 7 associations with physical health conditions have been less studied, despite health-care costs in ADHD being substantially driven by both psychiatric and physical comorbid conditions. 8 , 9 Physical conditions that have shown robust and replicated association with ADHD, especially in childhood, include metabolic disorders, sleep disorders, and asthma. 10 A few studies have suggested tentative associations between ADHD and dementia, 11 diseases of the basal ganglia and cerebellum (eg, Parkinson's disease), 12 and cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…The present study was designed to investigate the differences in suicidal ideation, temperament, and manic and hypomanic symptoms between patients with adult ADHD and healthy controls. ADHD in adulthood, especially when concurrent with other mental diseases, may lead to major consequences for public health, such as higher healthcare costs and more difficult patient management [11].…”
Section: Discussionmentioning
confidence: 99%
“…Higher healthcare utilization and costs for multimorbidity, especially for the inpatient care of psychiatric disorders, are generally reported among adults who have had childhood ADHD, remitted or not [11]. Many studies report the presence of comorbid psychiatric disorders in adults with ADHD [12][13][14] and also report ADHD in individuals with at least one psychiatric disorder [15].…”
Section: Introductionmentioning
confidence: 99%
“…Adolescents with ADHD are at increased risk of many adverse outcomes and a negative life trajectory into adulthood [3,4]. Appropriate treatment and care for this group will potentially reduce the risk of harmful outcomes and hence be cost-effective on many levels for individuals, families and society [5,6].…”
Section: Introductionmentioning
confidence: 99%